Retrospective analysis of adjuvant treatment of gastric cancer - Rolski, Janusz; Krzemieniecki, Krzysztof; Pawlicki, Marek; Ziobro, Marek; Zemełka, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2003)
The analysis concerned a group of 62 patients with primarily operating stomach who stayed for observation or treatment in the Clinic of Chemotherapy, Centre of Oncology Cracow Branch in the period from January 1990 to December 1997. The investigation involved patients after radical surgical procedure (in 52 patients, that is 83.9% subtotal gastrectomy and in 10 patients, that is 16.1% total gastrectomy were performed) in which at least one risk factor was confirmed: flow of serosa or surrounding tissues, presence of metastasis in regional lymph nodes or lack of microscopic radicality in the line of cut. 17 patients (27.4%) made up group A (subject to observation), 30 (48.4%) – group B (subject to chemotherapy: according to FAM or FAMtx) whereas 15 (24.2%) – group C (subject to chemoradiotherapy according to the following regime: 1 cycle of FAM chemotherapy then irradiation in conditions of therapy Co60 in dose 45 Gy onto tumor bed and regional lymphatic site and after its end additional 5 cycles of chemotherapy according to FAM). The period of observation carried out was a minimum of 5 years. 5-year overall survival in group A was 35.3%, in group B – 26.7% and in group C – 26.7%. The average time of overall survival in group A was 33.2 months, in group B – 28.8 months and in group C – 31.1 months. Statistical differences were not significant (p=0.7213). 5-year asymptomatic survival in group A was 35.3%, in group B – 23.3% and in group C – 26.7%. The average time of asymptomatic survival in group A was 31.1 months, in group B – 24.9 months and in group C – 30.6 months. Statistical differences were not significant (p=0.2955). The percentage of failures in group A was 52.9%, in group B – 66.7% and in group C – 46.7%. The type of failures (local, distant or local + distant) did not essentially differ between groups. The depth of invasion (p=0.0162) and stage (p=0.0071) had a statistical impact on the time of overall and asymptomatic survival.